PERAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MEMBANGUN KESEHATAN MENTAL SISWA DI SMP AL-FURQON MADRASATUL QUR'AN TEBUIRENG JOMBANG - Utomu Maulidi, Moh. Rois; Aida Arini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The mental health crisis among adolescents has become an urgent global concern. The WHO (2023) reports that over 20% of adolescents worldwide experience psychological disorders ranging from anxiety to clinical depression. In Indonesia, data from the Ministry of Health (2022) indicates that approximately 36% of school-age students suffer from mild to moderate health disturbances related to lifestyle and psychosocial pressures. Amid these challenges, Islamic Religious Education (IRE/PAI), with its holistic approach integrating spiritual, moral, and social dimensions, holds strategic potential as a mental health-building instrument, yet remains empirically underexplored. This study aims to: (1) describe IRE learning at SMP Al-Furqan Madrasatul Qur'an Tebuireng Jombang; and (2) analyze the role of IRE learning in building students' mental health through four indicators: managing personal potential, coping with stress, building positive social relationships, and managing emotions while contributing productively. A qualitative case study design was employed, with data gathered through in-depth interviews, participatory observation, and documentation involving the school principal, IRE teachers, counseling teachers, and students. Data analysis followed the Miles and Huberman model, validated through source and technique triangulation. Results reveal that IRE at SMP Al-Furqan operates holistically through experiential learning, supported by a pesantren-based ecosystem that integrates worship habituation, teacher exemplary conduct, and authentic assessment. Its role in mental health is evident across four pathways: developing personal potential through amanah-based guidance; building stress resilience through internalization of patience (sabar), trust in God (tawakkul), and prayer; cultivating positive social bonds through empathy and ukhuwah; and fostering emotional regulation and productive contribution through discipline and self-reflection (muhasabah).